2020
DOI: 10.1111/jcpp.13270
|View full text |Cite
|
Sign up to set email alerts
|

Developmental profiles of childhood attention‐deficit/hyperactivity disorder and irritability: association with adolescent mental health, functional impairment, and suicidal outcomes

Abstract: Background Irritability is frequently comorbid with ADHD. Although irritability alone has been linked to deleterious mental health and adaptive issues, the joint developmental course of ADHD and irritability symptoms during childhood as well as its association with later mental health and suicidal outcomes is not fully understood. We aimed to describe the developmental trajectories of childhood ADHD and irritability symptoms and to quantify their association with adolescent mental health and suicidal outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Both continuity and change over time were observed within trajectory groups, along with common and specific risk factors predicting group membership. Given the extensively documented maladaptive outcomes associated with internalising, externalising, and peer problems when examined individually (e.g., Bevilacqua et al, 2018 ; Rivenbark et al, 2018 ; Fairchild et al, 2019 ; Gutman & McMaster, 2020 ; Galera et al, 2021 ; Orri et al, 2018 ), identification of comorbid and multimorbid trajectories using a population-based sample, along with a better understanding of antecedent risk factors associated with group membership, sheds several important new insights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both continuity and change over time were observed within trajectory groups, along with common and specific risk factors predicting group membership. Given the extensively documented maladaptive outcomes associated with internalising, externalising, and peer problems when examined individually (e.g., Bevilacqua et al, 2018 ; Rivenbark et al, 2018 ; Fairchild et al, 2019 ; Gutman & McMaster, 2020 ; Galera et al, 2021 ; Orri et al, 2018 ), identification of comorbid and multimorbid trajectories using a population-based sample, along with a better understanding of antecedent risk factors associated with group membership, sheds several important new insights.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small percentage of children, between 5–10%, within population-based studies (e.g., Girard et al, 2019 ; Nagin & Tremblay, 1999 ; Odgers et al, 2007 ; Shaw et al, 2003 , 2005 ) have been found to continue with elevated chronic levels of aggression and conduct problems into and across adolescence. Population-based studies have suggested higher levels, between ~ 15–20% of children, with elevated chronic levels of hyperactivity/inattention from childhood to adolescence (e.g., Galéra et al, 2011 , 2021 ; Pingault et al, 2013 ; Shaw et al, 2005 ), with up to 40% having continuing and elevated levels into adulthood (e.g., Daley, 2006 ). On the other hand, internalising problems (e.g., emotional problems, anxious/depressed and withdrawn) are more likely to increase from early childhood onwards, particularly for girls (e.g., Gilliom & Shaw, 2004 ; Leve et al, 2005 ).…”
mentioning
confidence: 99%
“…Multiple studies have investigated the epidemiology and risk factors for suicidal ideation and attempt from the perinatal period to adolescence [29,47,48,64,65,69,[80][81][82][83][84]. In the QLSCD, lifetime prevalence of passive suicidal ideation (13-17 years old), serious suicidal ideation, and suicide attempt (13-20 years old) are 22.2%, 9.8%, and 6.7%, respectively [82].…”
Section: Suicidal Ideation and Suicide Attemptsmentioning
confidence: 99%
“…Therefore, future genetically informed designs are necessary to test this hypothesis (Pingault et al, 2018). Finally, previous studies point to the key role of impulsive-aggression (and related behaviors, such as irritability and hyperactivity) in both the etiology of suicide attempt (Galera et al, 2020;Orri, Galera, et al, 2018;Orri, Perret, et al, 2018; and the intergenerational transmission of suicide risk ( McGirr et al, 2009;McGirr & Turecki, 2007;, especially among youth (McGirr et al, 2008). Impulsive-aggression is highly heritable and genetically associated with smoking (Liu et al, 2019), thus it is likely to be an important mechanism explaining our results.…”
Section: Discussionmentioning
confidence: 72%